Chair-Based Exercise is An Effective Method For Improving Cognitive Function and Quality of Life in The Elderly - Diana Pefbrianti; M Noor Ifansyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The community service partner is the elderly and families in Tambak Baru Ilir Village. There are still many elderly people who suffer cognitive impairment and decreased quality of life. Most elderly people ignore this because they don't think it's physically threatening, leading to the elderly becoming dependent on others around them. Elderly and families need to be socialized about non farmacology treatment to solve this problem, such as chair based exercise. Chair Based Exercise (CBE) is a structured physical exercise intervention carried out in a sitting position, specifically designed for elderly people with physical limitations, weaknesses, or those at high risk of falling. CBE to address issues caused by cognitive impairment and decreased quality life through skrinning cognitive function and quality of life in the elderly, demonstrated for 60-minute exercise session for 25 elderly individuals. The result of the CBE demonstration was that the elderly and their families feel enthusiastic about this activity. In kognitif function, majority elderly are in intact cognitive function category and all are in the moderate quality of life category. CBE can have a positive impact on elderly individuals who face issues due to cognitive impairment and decreased quality of life, helping them to maintain their lives and continually respond to their surrounding environment.